Mobile Cellular Technology Forecast for the Indonesian Telecommunications Industry - Hidayat, Taufik; Mahardiko, Rahutomo; Alaydrus, Mudrik (Journal of Telecommunications and the Digital Economy, 2020)
Current mobile telecommunications deployment in Indonesia, based on 2G, 3G and 4G technologies, lags behind many other developing countries because of Indonesia’s larger territory. This paper presents recent data on revenue growth (%) and the number of Base Transceiver Stations (BTSs) in Indonesia, divided among 2G, 3G and 4G technologies, and forecasts future revenue growth and numbers of BTSs for the next few years. The results show that, while revenue growth from 2G operation is decreasing and 4G deployment is significantly increasing, there are still significant revenues from 2G services and many 2G BTSs in operation at the end of the forecast period, making it difficult to shut down the 2G networks in the near future.